Typical Patterns of Bone Involvement in Whole-Body MRI of Patients with Chronic Recurrent Multifocal Osteomyelitis (CRMO) - von Kalle, T.; Heim, N.; Hospach, T.; Langendörfer, M.; Winkler, P.; Stuber, T. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: The diagnosis of CRMO often involves a long patient history. We evaluated the spectrum of bone involvement in whole-body magnetic resonance imaging (WB-MRI) and assessed its potential contribution to a more rapid diagnosis.Materials and Methods: WB-MRI (1.5 T, coronal STIR sequences) in 53 children and adolescents (mean age 11 years, 4.8 – 15.1) with histologically (n = 37) or clinically (n = 16) confirmed CRMO were retrospectively reviewed by two experienced pediatric radiologists.Results: WB-MRI revealed multifocal lesions in all but one patients. Only 26 of them had presented with multifocal complaints. We detected 1 – 27 geographic lesions/patient (mean 9.7). 510 of 513 lesions were significantly hyperintense compared to normal bone marrow. The pelvis, lower extremities, shoulders and spine were most frequently involved. 40 patients (75 %) had bilateral symmetrical involvement of bones. Most of the lesions were located in tubular bones, in 87 % adjacent to one or both sides of a growth plate. 32 % of lesions showed periosteal involvement. Of 456 affected bones, 33 (7.2 %) were deformed, 6 (18 %) were vertebra plana.Conclusion: In the absence of more specific diagnostic criteria, WB-MRI can, in synopsis with clinical findings, substantially contribute to a rapid diagnosis of CRMO. It discovers the typical pattern of multifocal and bilateral bone involvement more often than has been reported for targeted MRI. It readily reveals the characteristic proximity of lesions to growth plates, the sacroiliac joint and triradiate cartilage and helps to uncover asymptomatic spinal complications.
Keywords: bones; MR imaging; non-bacterial chronic osteomyelitis; children; adolescents